Wind power and irrigation - Rader, Frederick Ellsworth (My University, 1895)
Introduction: There was a time when wind and water were the only natural motive forces at man’s command. They are both forces of nature made subservient by man for industrial purposes. We may witness the destructive effects of the wind in the storms, tornadoes, and in the path of the much dreaded cyclone. That it may be a power for good may be seen from the numerous white sails that dot our seas, carrying our commercial interests, that, in some places, competes successfully with steam. Beautiful Holland is partially reclaimed from the sea by the aid of the motive force of the wind properly applied. There the well known “Dutch” mills have been used for ages, source of them it is claimed have with stood storm and wind for over five hundred years. They were used for both pumping and grinding, and their peculiar construction makes their appearances, during motion, interesting and suggestive.
Citation: Rader, Frederick Ellsworth. Wind power and irrigation. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Wind power; Irrigation; Energy; Theses; Manuscripts (documents)